Synthesis and Evaluation of N-(3-Trifluoroacetylindol- 7-yl) Acetamides for Potential In Vitro Antiplasmodial Properties - Malose J., Mphahlele; Mmakwena M., Mmonwa; Yee, Siew Choong (MDPI, 2017)
A series of novel N-((2,5-diaryl-3-trifluoroacetyl)-1H-indol-7-yl)acetamides has been prepared via a successive and one-pot reaction sequence involving initial trifluoroacetic acid-mediated Beckmann rearrangement of the oximes derived from the 1-(2,5-diaryl-1H-indol-7-yl)ethanones, followed by trifluoroacetylation of the incipient N-(2,5-diaryl-1H-indol-7-yl)-acetamides with trifluoroacetic anhydride. The prepared compounds were evaluated for potential in vitro antiplasmodial properties. Preliminary results from antiplasmodial activity against the chloroquine-sensitive 3D7 strain of Plasmodium falciparum revealed that a combination of 2-(4-flurophenyl)- and 5-(4-fluorophenyl) or 2-(4-flurophenyl)- and 4-fluorostyryl groups in compounds 3(a,f) and 4(a,g), for example, is required for biological activity for both series of compounds. Their possible mode of action against the plasmodial parasite is explained theoretically through molecular docking of the most active compounds against the parasite lactate dehydrogenase (pLDH). These compounds were docked at the entrance of NAD+ in pLDH presumably hindering entry of lactate to cause the observed inhibition effect of pLDH. The four compounds were found to exhibit low toxicity against monkey kidney Vero cells at the highest concentrations tested.